Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T20:10:11+01:00
A) a²+b²=c²
0,6²+0,9²=x²
0,36+0,81=x²
x²=1,17
x≈1,1≈1

b) a²+b²=c²
x²+1,5²=2²
x²+2,25=4
x²=4-2,25
x²=1,75
x≈1,3≈1
9 4 9
2010-02-01T20:10:57+01:00
0,6²+0,9²=x²
1,17=x²
x=1,082m

b)
1,5²+x²=2²
2,25+x²=4
x²=1,75
x=1,323m
4 2 4
2010-02-01T23:50:21+01:00
A)
przeciw prostokątna=x²
przyprostokątne=0,6m i 0,9m
a²+b²=c²
(0,6)²+(0,9)²=x²
0,36+0,81=x²
x²=1,17
x=1,08≈1,1m

b)
przeciwprostokątna=2m²
przyprostokątne=x² i1,5m²
a²+b²=c²
x²+(1,5)²=2²
x²+2,25=4
x²=4-2,25
x²=1,75
x=1,323≈1,3m
3 4 3